THE FUTURE OF OCCUPATIONAL HEALTH AND SAFETY: BIBLIOMETRIC ANALYSIS & NARATIVE REVIEW OF AI IMPLEMENTATION IN INDUSTRY 5.0 - irsan hadi; Agus Wibowo (Informatika: Jurnal Teknik Informatika dan Multimedia, 2025)
The research studied how Artificial Intelligence (AI) is applied to Occupational Health and Safety (OHS) during the industry 5.0 period. Through a bibliometric method and complemented with a narrative review, this study systematically investigates the existing literature with a focus on trends, challenges, and opportunities brought about by the implementation of AI in workplace safety. Based on analysis of 383 publications released from well-renowned journals covering previous 5 years time frame, it was concluded that AI is pivotal in enhancing all industrial sectors' safety mechanisms. The findings indicate that AI technology can significantly enhance the safety of work environments and can lead to better health outcomes through predictive analysis and continuous monitoring. Even so, the study also uncovered major gaps, particularly regarding fair access to the benefits of AI society-wide and by industry sector. The findings of this study highlight the potential for AI to enhance OSH but recognise an urgent need for cross-disciplinary research in this field to fill the identified gaps and confirm an inclusive approach. These findings make an important contribution to the ongoing discussion on AI in OSH, as well as providing valuable insights for researchers, policymakers, and industry practitioners seeking to create a safer and more sustainable work environment.